2019
DOI: 10.1101/739094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal subfield volumes are uniquely affected in PTSD and depression: International analysis of 31 cohorts from the PGC-ENIGMA PTSD Working Group

Abstract: Background: PTSD and depression commonly co-occur and have been associated with smaller hippocampal volumes compared to healthy and trauma-exposed controls. However, the hippocampus is heterogeneous, with subregions that may be uniquely affected in individuals with PTSD and depression. Methods:We used random effects regressions and a harmonized neuroimaging protocol based on FreeSurfer (v6.0) to identify sub-structural hippocampal markers of current PTSD (C-PTSD), depression, and the interaction of these condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…To further understand the role of the hippocampus in depression and affective disorders, recent work from the ENIGMA consortium has begun to examine volumetric abnormalities in subfields of the hippocampus. In a recent study of participants with varying levels of trauma exposure, Salminen et al [2019b] showed that depression, but not PTSD, was associated with smaller volumes in the hippocampal CA1 and hippocampal tail. Sex-stratified analyses showed this effect was specific to females.…”
Section: Major Depressive Disordermentioning
confidence: 98%
See 1 more Smart Citation
“…To further understand the role of the hippocampus in depression and affective disorders, recent work from the ENIGMA consortium has begun to examine volumetric abnormalities in subfields of the hippocampus. In a recent study of participants with varying levels of trauma exposure, Salminen et al [2019b] showed that depression, but not PTSD, was associated with smaller volumes in the hippocampal CA1 and hippocampal tail. Sex-stratified analyses showed this effect was specific to females.…”
Section: Major Depressive Disordermentioning
confidence: 98%
“…Given the significant effect in the hippocampus from the subcortical meta-analysis, our group recently completed a prospective mega-analysis of hippocampal subfield markers of PTSD, and the effect of comorbid depression. Specifically, Salminen et al [2019b] showed that the effect of depression was stronger than the effect of PTSD in the whole sample and in females, but not in males. Females with depression showed smaller volumes in the hippocampal tail and CA1 subfield compared to those without depression and were not significantly affected by PTSD.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 98%
“…In addition to the samples that could be allocated to the four subgroups, the ENIGMA-Anxiety database contains information on samples with anxiety disorder diagnoses that are not an immediate focus of investigation; these samples concern, for example, children with separation anxiety (Calkins et al, 2015;Salum et al, 2011;Salum et al, 2015;Satterthwaite et al, 2014), children at risk for developing an anxiety disorder (Battaglia et al, 2012;Fu, Taber-Thomas, & Pérez-Edgar, 2017;Taber-Thomas, Morales, Hillary, & Pérez-Edgar, 2016), participants with anxiety-related traits and at risk phenotypes (Campbell-Sills et al, 2011;Dannlowski et al, 2015;Dannlowski et al, 2016;Mujica-Parodi et al, 2009; alterations in the microstructure of white matter tracts based on DTI data (Kochunov et al, 2015), in the connectivity of brain functional networks utilizing resting-state functional (f)MRI (Adhikari et al, 2018), and in the responsivity of brain regions to anxiety-related cues utilizing task-related functional (f)MRI paradigms (under development). Then, ENIGMA approaches that assess more subtle variations in brain morphology including investigation of regional subfields (e.g., of hippocampus and amygdala (Salminen et al, 2019;Saygin et al, 2017)), subcortical shape (Ching et al, 2020;Gutman et al, 2015;Gutman, Wang, Rajagopalan, Toga, & Thompson, 2012;Ho et al, 2019), and brain asymmetry (Kong et al, 2018), can be key next steps.…”
Section: The Start and Structure Of The Enigma-anxiety Working Groupmentioning
confidence: 99%
“…Segmentation of hippocampal subfield volumes using lower resolution (1 mm 3 ) MRI ( Ahmed-Leitao et al, 2019 ; Chen et al, 2018 ; Hayes et al, 2017 ; Salminen et al, 2019 ), has also been performed to characterize hippocampal changes in individuals with PTSD. These studies have reported either reduced volume of the DG ( Hayes et al, 2017 ), CA1 and CA3 ( Chen et al, 2018 ), or no differences in subfield volumes in the PTSD population ( Ahmed-Leitao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported either reduced volume of the DG ( Hayes et al, 2017 ), CA1 and CA3 ( Chen et al, 2018 ), or no differences in subfield volumes in the PTSD population ( Ahmed-Leitao et al, 2019 ). A recent report also suggested that changes in CA1 are rooted in the interaction between comorbid depression and PTSD ( Salminen et al, 2019 ). However, given that the most important anatomical landmarks for subfield labeling (i.e., the thin band formed by the inner lamina of the CA and the outer lamina of the DG) are not visible at this lower resolution, the segmentation process is less reliable and consistent across individuals ( de Flores et al, 2015 ; Iglesias et al, 2015 ; Wisse et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%